ChemInform Abstract: Asymmetric Hydrogenation of Olefins Using Chiral Crabtree‐Type Catalysts: Scope and Limitations. Issue 16 (22nd April 2014) - Verendel, J. Johan; Pamies, Oscar; Dieguez, Montserrat; Andersson, Pher G.
Abstract Review: 273 refs.